Windsor chairmaking - Mursell, James (Crowood, 2009)
Windsor chairs are a beautiful and traditional feature in any home. Celebrate their history, and learn their heritage. Both novice and experienced woodworkers can learn how to make a Windsor chair that is both functional and beautifully shaped